Burns, Sepsis and Procalcitonin - T. G. Spiridonova; E. A. Zhirkova; A. V. Sachkov; S. S. Petrikov (Неотложная медицинская помощь)
The basis of the pathogenesis of burn disease is a systemic inflammatory response syndrome with episodes of bacteremia and the development of sepsis. An analysis of the literature showed that the existing clinical diagnostic scales for sepsis do not allow a confident diagnosis. The interest in changes in the concentration of procalcitonin in the blood serum is justified by the fact that this prohormone is one of the proinflammatory mediators, the concentration of which quickly increases during local and systemic bacterial and fungal infections. It seems important to consider the possibilities of various scales for determining the criteria for sepsis, analyze the values of procalcitonin and its monitoring for more effective diagnosis and procalcitonin-controlled antibiotic therapy in patients with burns.CONCLUSION. The problem of clinical diagnosis of sepsis in patients with burns has not yet been solved. Procalcitonin is an effective biomarker of bacterial infection, and its monitoring reflects the dynamics of the burn disease, predicts the outcome, indicates the effectiveness of antibiotic therapy and allows for its correction.